Assessment and Prioritization of BIM Implementation Challenges in Residential Complexes in Iraq (Journal of Engineering, 2026)
This study investigated the challenges of implementing Building Information Modeling (BIM) in residential complexes in Iraq. The research will aim at determining the most prominent challenges that have affected the implementation of BIM, evaluating the challenges based on the perceptions of the professionals, and presenting practical insights that can be used to realize successful implementation. The mixed-method research design was applied, and it included the literature review, expert interviews, and a questionnaire survey of 67 professionals who were involved in the construction projects. The identified challenges were ranked using the collected data with the help of Reliability testing and Relative Importance Index (RII). The findings are that the most threatening impediments to BIM implementation are the human and organizational factors. Particularly, the technical unawareness and BIM perception, along with the insufficiency of training and competence, were put first on the list of the most crucial challenges. Further, there was poor senior management support and the absence of an enabling organizational environment, which was noted to be a barrier to BIM adoption. Financial and infrastructural issues, such as the software and the internet connectivity, on the other hand, were considered to have a lesser effect. The conclusion is that the successful use of BIM in residential complexes in Iraq should be oriented on a complex approach with capacity building, organizational commitment and the development of effective national policies and regulatory frameworks to support the digital revolution in housing industry.